2022
DOI: 10.37715/jtce.v2i1.2180
|View full text |Cite
|
Sign up to set email alerts
|

The role of tour manager in assessing and planning travel opportunities in Covid-19 new normal era for the locals

Abstract: Indonesia tourism should make a move if it has superior and quality tourism resources. The travel sector feels the impact of the pandemic Covid 19 but recovering in their efforts and continue to prioritize on tourism as its main business. Tour Manager must develop a new strategic tour plan by taking advantage of potential opportunities for local communities as their partners. This qualitative research uses descriptive approach in describing the research problems above and answer three research questions, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results of observations on tourist attractions also revealed that Selayar Islands Regency possesses a variety of interesting tourist attractions. The results also suggest that the (Deng, Weng, & Wu, 2022;Wahyuningputri, Hendra, Putra, & Djati, 2022) and is a worthy representative of tourist destinations on the website. The analysis of the tour package components determines the required content display.…”
Section: Figure 5 Tourist Destinations Displaymentioning
confidence: 65%
“…The results of observations on tourist attractions also revealed that Selayar Islands Regency possesses a variety of interesting tourist attractions. The results also suggest that the (Deng, Weng, & Wu, 2022;Wahyuningputri, Hendra, Putra, & Djati, 2022) and is a worthy representative of tourist destinations on the website. The analysis of the tour package components determines the required content display.…”
Section: Figure 5 Tourist Destinations Displaymentioning
confidence: 65%